2007
DOI: 10.1021/ed084p1998
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalytic Activity of Ruthenium–Indenylidene Complexes for Olefin Metathesis

Abstract: A series of experiments for undergraduate laboratory courses (e.g., inorganic, organometallic or advanced organic) have been developed. These experiments focus on understanding the design and catalytic activity of ruthenium–indenylidene complexes for olefin metathesis. Included in the experiments are the syntheses of two ruthenium–indenylidene complexes that can be conveniently prepared from commercially available starting materials. The two complexes differ only by the nature of the phosphine ligand, yet each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In recent years, the development and application of ruthenium indenylidene type catalysts 133 has received widespread attention due to their high activity in various olefin metathesis reactions and their comparable ease of synthesis. 134 We have previously stressed the importance of straightforward synthetic routes to ruthenium alkylidene complexes, and ruthenium indenylidene complexes, readily prepared upon reaction of propargylic alcohol and Cl 2 Ru(PPh 3 ) 3-4 , are interesting candidates in this respect. Moreover, most of the reported ruthenium indenylidene complexes exhibit high air and moisture stability, good thermal stability, and excellent tolerance toward functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development and application of ruthenium indenylidene type catalysts 133 has received widespread attention due to their high activity in various olefin metathesis reactions and their comparable ease of synthesis. 134 We have previously stressed the importance of straightforward synthetic routes to ruthenium alkylidene complexes, and ruthenium indenylidene complexes, readily prepared upon reaction of propargylic alcohol and Cl 2 Ru(PPh 3 ) 3-4 , are interesting candidates in this respect. Moreover, most of the reported ruthenium indenylidene complexes exhibit high air and moisture stability, good thermal stability, and excellent tolerance toward functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Ring opening metathesis polymerization (ROMP) exploits the metathesis equilibrium by using the relief of ring strain to drive the formation of, often trans, double bonds (Scheme 11). Typical monomers are cyclooctene, cyclooctadiene, norbornene, and norbornadiene derivatives (40)(41)(42)(43)(44)(45)(46). Monomers with functional groups, e.g.…”
Section: Scheme 10 General Reaction Scheme Of Olefin Metathesis (Sementioning
confidence: 99%
“…Recent work in chemical education has shown that students display great interest and enthusiasm in learning sustainable methods and laboratory exercises showing how chemists can implement changes in future chemical processes. Multiple laboratory exercises address the aspects of transition-metal catalysis and mechanochemistry for undergraduate students, but combining both techniques and showing students how chemical processes are adapted over time to achieve increased sustainability has been, to the best of our knowledge, overlooked. The recent development of a new synthetic methodology for [Cu­(Cl)­(NHC)] complexes provides an excellent opportunity to create a new laboratory experiment for undergraduate students in which green chemistry, mechanochemistry, and catalysis aspects are introduced simultaneously.…”
Section: Introductionmentioning
confidence: 99%